2009
DOI: 10.1007/s00383-009-2439-2
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of clinical outcome in patients with total intestinal aganglionosis

Abstract: Total intestinal aganglionosis (TIA) is the most extreme and rare form of Hirschsprung disease (HD). Until few years ago TIA was considered to be a uniformly fatal condition. Survival has improved in the recent years with the advent of parenteral nutrition, innovative surgical techniques and small bowel transplantation. The purpose of this meta-analysis was to determine the clinical outcome of TIA following various surgical procedures. A meta-analysis of cases of TIA reported in the literature between 1985 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…77 However, in about 1% of cases, Hirschsprung's disease is characterized by total intestinal aganglionosis, for which a high mortality rate has been described (66.2% of 68 patients). 78 When intestinal resection of the aganglionic tract determines SBS needing HPN, prognosis is similar to that of SBS. 79,80 In children, the absence of a specialist nutritional care team was a significant risk factor for mortality.…”
Section: Patient Populationmentioning
confidence: 96%
“…77 However, in about 1% of cases, Hirschsprung's disease is characterized by total intestinal aganglionosis, for which a high mortality rate has been described (66.2% of 68 patients). 78 When intestinal resection of the aganglionic tract determines SBS needing HPN, prognosis is similar to that of SBS. 79,80 In children, the absence of a specialist nutritional care team was a significant risk factor for mortality.…”
Section: Patient Populationmentioning
confidence: 96%
“…According to the length of the affected segment, 80% of patients are classified as short‐segment HSCR, 15% of cases are classified as long‐segment HSCR, and the remaining 5% of cases unfortunately show involvement of the entire colon and small intestine . Ultimately, the disease manifests as distal intestinal obstruction neonatally, chronic constipation in older children, or enterocolitis due to the disordered development of enteric neurons in the distal gut . Although surgical options such as “pull‐through” surgery or colostomy have been a consensus therapy and performed in clinical practice for years, the pathogenesis of HSCR remains unclear …”
Section: Introductionmentioning
confidence: 99%
“…Intestinal transplantation is emerging as a potential option for these children. 34 On the other hand, Diamanti et al 35 found good quality of life in a small group of children with ultra-short bowel syndrome. Although still dependent on parenteral nutrition, the children regularly attended school and none was listed for intestinal transplantation.…”
Section: Re 1 Dealing With a Complicated And Severe Congenital Anomalymentioning
confidence: 98%